The Oslo Museum Puzzle. Reflections on the relation between culture and economy - Skrede, Joar (FormAkademisk, 2011)
The decision has been made to relocate several cultural institutions in Oslo, without any existing plans for the old premises. In this article, the supportive arguments are analysed against the backdrop of the critical voices. The critics want to preserve the old buildings because they are embedded in the nation’s collective memory and have value as history. The supporters of the plans argue that the new buildings are bricks in a bigger city renewal project and shall generate synergetic effects beyond just functioning as cultural institutions. Critical discourse analysis is used eclectically as a methodological framework with a specific focus on what structural patterns of social change the arguments imply. The conclusion is that economy’s entry into the cultural sphere may be a threat to the cultural heritage.